Towards an efficacious system of internationalization of higher education in VietNam at present time - Thái, Thanh Sơn (Đại học Quốc gia Hà Nội, 2020)
In this short paper we hope to be able to explain to this audience of high qualified specialists our simple remarks leading to first imagination of some models for a system of IHE in Vietnam.1. WHY? Firstly, we’d like to determine the reason why Internationalization in Higher Education needs to be realized and developed faster and stronger in Vietnam at the present time.2. WHO? In this second part, we try to analyze the target groups of potential learners who should attend and could benefit from IHE in Vietnam, after some principal and most important criteria.3. WHAT? In the third part of our presentation we propose some principal fields of specialties most needed for the current social economic development in Vietnam, and the most important skill and know-how to be trained for future learners through IHE. We also try to propose the content of training curriculum in these specialties which will cope with the current demand of the economy. 4.HOW? Basing on the determination of the potential learners mentioned above, we propose some most suitable forms of training, criteria for choosing international partners. For conclusion, we refer to the problem of organization of an efficacious system of IHE as well as to touch the problem of criteria of national human resource we need to prepare for working in this system